2005
DOI: 10.7326/0003-4819-142-11-200506070-00008
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Endoscopy Is Not a Major Risk Factor for Transmitting Hepatitis C Virus

Abstract: These findings support the hypothesis that properly performed digestive endoscopy is not a major risk factor for the transmission of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 18 publications
4
28
0
2
Order By: Relevance
“…Hence, it seems that countries with a higher HCV prevalence are likely to concentrate a significant proportion of HCV carriers in health-care facilities and, when this is associated with insufficient adherence to standard safety measures the risk of nosocomial transmission is considerable. That such measures minimize nosocomial infection rates has been shown in a survey in which no seroconversion was detected among 912 patients undergoing endoscopy with properly disinfected instruments used in HCVinfected patients [114].…”
Section: Improvement In Safety Of Health-care-related Proceduresmentioning
confidence: 98%
“…Hence, it seems that countries with a higher HCV prevalence are likely to concentrate a significant proportion of HCV carriers in health-care facilities and, when this is associated with insufficient adherence to standard safety measures the risk of nosocomial transmission is considerable. That such measures minimize nosocomial infection rates has been shown in a survey in which no seroconversion was detected among 912 patients undergoing endoscopy with properly disinfected instruments used in HCVinfected patients [114].…”
Section: Improvement In Safety Of Health-care-related Proceduresmentioning
confidence: 98%
“…Several studies found that GI endoscopic procedures were associated with HCV infection (175)(176)(177)(178). Other clinical studies monitored HCV-negative patients who underwent GI endoscopy with the same endoscopes as those used on HCV-positive patients (179,180). It was concluded that the risk for HCV transmission by endoscopy is low when adequate endoscope reprocessing is used.…”
Section: Hepatitis B Virus Hepatitis B Virus (Hbv) Is a Highly Infecmentioning
confidence: 99%
“…For instance, cases of HCV patient-to-patient infection after colonoscopy, were clearly associated with reprocessing colonoscopies and devices flaws 6 . In fact, viruses are supposed to be easily eliminated and epidemiologic studies have confirmed that endoscopy is very safe in this regard 7,8 . Nevertheless, endoscopes comprise a high bioburden of microorganisms after use have incorporated many additional invasive procedures, and are difficult to clean and disinfect because they are delicate and display a complex design 9,10 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%